To calculate \((f \cdot g)(x)\), we need to multiply the functions \(f(x)\) and \(g(x)\):
- The function \(f(x) = x\) represents the length of the rectangle.
- The function \(g(x) = x + 3\) represents the width of the rectangle.
Now, we compute the product:
\[ (f \cdot g)(x) = f(x) \cdot g(x) = x \cdot (x + 3) = x^2 + 3x \]
The expression \(x^2 + 3x\) represents the area of the rectangle in square feet.
Thus, the correct response is:
\[ (f \cdot g)(x) = x^2 + 3x; \text{ It represents the area of the rectangle in square feet.} \]